Kartu Positif Negatif Sebagai Alternatif Pemahaman Konsep Operasi Hitung Bilangan Bulat Pada Siswa Kelas V SD Negeri 18 Klawasi Kota Sorong - Trisnawati, Nika Fetria; Yuliani, Nova; Levina, Anna; Sundari; Musa'ad, Faida; Anwar, Zakiyah (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2024)
Community service aims to increase understanding of the concept of integer arithmetic operations, considering the importance of understanding and mastery of this material because it is the basic material for the next material. The research method of community service is learning using concrete examples such as positive (+) and negative (-) cards and borrowing. This community service activity took place over three meetings, starting on May 21, 25, and 27, 2024 with a total of 26 class V participants. Based on the results of observations during the activity, several positive things were obtained, namely: 1). The enthusiasm for learning that is very visible from students because of the fun learning process, 2). Courage that will foster students' self-confidence when coming forward to answer a question, and 3). Changes in the mindset of students who still think that mathematics is a difficult, stressful, and boring subject. This community service activity also has a very significant impact on changes in the increase in the value obtained by students in solving a problem.